2021
DOI: 10.3340/jkns.2021.0004
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Association of Psoas and Masseter Muscles with Traumatic Brain Injury Using Computed Tomography Anthropometry

Abstract: Objective : Psoas and masseter muscles are known markers of sarcopenia. However, the relative superiority of either muscle as a marker is unclear. Therefore, this study analyzed the two muscles in patients with a prognosis of traumatic brain injury (TBI). Methods : Patients with TBI visiting a regional trauma center between January 2017 and December 2018 were selected, and their medical records were reviewed. TBI patients with an abbreviated injury score (AIS) of 4 or 5 were selected. Patients with an AIS of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some authors found an association between low masseter mass and mortality in elderly patients after trauma 17 19 . In contrast, others did not confirm the prognostic relevance of the masseter for the same clinical condition 20 , 21 . CT-assessed low masseter mass has also been linked to postoperative pneumonia in oesophageal cancer 22 , carotid endarterectomy 23 , 24 , and stroke outcome 25 .…”
Section: Introductionmentioning
confidence: 93%
“…Some authors found an association between low masseter mass and mortality in elderly patients after trauma 17 19 . In contrast, others did not confirm the prognostic relevance of the masseter for the same clinical condition 20 , 21 . CT-assessed low masseter mass has also been linked to postoperative pneumonia in oesophageal cancer 22 , carotid endarterectomy 23 , 24 , and stroke outcome 25 .…”
Section: Introductionmentioning
confidence: 93%
“…It was found that PMI was statistically significant as a risk factor for mortality (P = 0.023; OR = 0.715). A statistically significant correlation was found between PMI and Glasgow Outcome Scale (GOS) score (correlation coefficient, 0.168; P = 0.003) [66]. Supplemental Table 2 lists the studies searching for associations between PMI and other CT-measured anthropomorphic variables and outcomes in trauma patients.…”
Section: Pma Assessment In Patients With Traumamentioning
confidence: 99%
“…It has been used to predict outcomes in carotid endarterectomies [8,9] and strokes [10]. Specific to trauma, 4 studies have looked into masseter area measurements as a prognostic parameter [11][12][13][14]. In 2016, Wallace et al introduced the role of the masseter as a sarcopenia surrogate in a large retrospective cohort study in trauma patients aged above 65 years [11].…”
Section: Introductionmentioning
confidence: 99%
“…Masseter sarcopenia in severe traumatic brain injury has also been shown to be predictive of 30-day mortality and the need for longer-term acute facilities or rehabilitation on discharge [12]. However, a recent Korean study involving patients with traumatic brain injury of all ages negated statistical prognostic value of masseter measurements, but supported the correlation of psoas measurements with mortality and Glasgow outcome score [14].…”
Section: Introductionmentioning
confidence: 99%